THE ROLE OF MOTIVATION IN SECOND LANGUAGE LEARNING SUCCESS (Ustozlar uchun, 2026)
Motivation is really important for people who want to learn a language. People who are motivated do when they are learning a language. They keep trying. They get more involved. They also do better than people who are not motivated. This article is about motivation. How it helps people learn a second language. It looks at the types of motivation and how they affect learning. It also looks at what things can influence motivation. The article wants to know how teachers and classrooms can help motivate students to learn. What they found out is that motivation comes from inside and outside. When teachers are good and the classroom is a place to be it really helps people learn a second language.Motivation from inside which is called motivation and motivation from outside which is called extrinsic motivation both make a big difference when people are learning a second language. They are important for second language learning success. Second language learning success is what this article is really about. It is, about how motivation and other things can help people learn a language (Dörnyei, 2005; Gardner, 2010).